Mineralogy and Petrology of Unique Native-Iron Basalts from Northern Siberia - Sara Mills (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2015)
Native iron, as a mineral, occurs in only three (3) geologic locations on Earth: 1) Disko Island (Greenland), 2) Bühl basalt (Kassel, Germany), and 3) Siberian flood basalts (SFB) (Taylor et al., 2014). Hypabyssal (shallow) mafic intrusions associated with the SFB in Northern Siberia contain metallic native iron, indicating formation under highly reducing environments (Olivine compositions clustered around Fo50, indicating crystallization from a parental magma with Mg# = 23 (MgO/FeO+MgO). This differs greatly from typical basalts from this region, which have been reported to have an Mg# between 50-60 (Wooden et al. 1993; Naldrett et al. 1992). Pyroxenes are present as augite and pigeonite, with compositions in equilibrium with those of olivine. Fine-grained matrix crystals of plagioclase are similar in composition to the cores of zoned grains, values ranging from An46-84 andAn43-82, respectively. Likewise, plagioclase phenocrysts are similar in composition to the rims of zoned grains, with compositions ranging from An54-80 and An54-77, respectively. These results show that the reduction process resulted in substantial enrichment of FeO in the melt, which is especially reflected in the compositions of pyroxene and olivine. This process also significantly reduced the oxygen fugacity to a point at which native iron became stable, a state which is almost exclusively found on extra-terrestrial bodies. Native iron in this sample occurs as the mineral kamacite (FeNi), with 1-3 wt% Ni. Other Fe-rich and terrestrially rare and unusual minerals found in this sample include: cohenite – Fe3C; native Cu; ilmenite – FeTiO3; troilite – FeS; chalcopyrite – CuFeS2; and wüstite – FeO.